Sexual selection in the Kinda baboon. Issue 135 (October 2019) - Petersdorf, Megan; Weyher, Anna H.; Kamilar, Jason M.; Dubuc, Constance; Higham, James P.
Abstract: Due to wide variation in the presence and degree of expression of a diverse suite of sexually-selected traits, the tribe Papionini represents an outstanding model for understanding how variation in sexual selection pressures and mechanisms leads to trait evolution. Here, we discuss the particular value of Papio as a model genus for studies of sexual selection, emphasizing the presence of multiple mating systems, and differences in the expression of sexually-selected traits among closely-related species. We draw particular attention to the Kinda baboon ( Papio kindae ), a comparatively less-studied baboon species, by providing a primer to Kinda baboon morphology, genetics, physiology, and behavior. Based on observations of large group sizes, combined with low degrees of sexual dimorphism and large relative testis size relative to other baboon species, we test the hypothesis that Kinda baboons have evolved under reduced direct, and increased indirect, male–male competition. We present the first long-term data on wild Kinda baboons in Zambia. Kinda baboon females show seasonal peaks in births and reproductive receptivity, and males exhibit a queing-rather than contest-based dominance acquisition with long alpha-male tenure lengths. We finish by making a number of explicit testable predictions about Kinda baboon sexual signals and behaviors, and suggest that Kinda baboons have potential to offer new insights into the selective environments that may have been experienced during homininization.